2008
DOI: 10.1007/s10384-008-0577-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of topical cyclosporin A 0.05% in conjunctival impression cytology specimens and clinical findings of severe vernal keratoconjunctivitis in children

Abstract: Topical CsA 0.05% eyedrops were found to be safe and effective in the treatment of patients with VKC. Consistent with these results, topical CsA may efficiently reduce conjunctival inflammation in severe VKC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 32 publications
1
42
0
Order By: Relevance
“…(18) There are several studies about low-dose topical CsA therapy for AKC and VKC. (9,(19)(20)(21) A study by Ozcan et al, which examined the use of topical CsA 0.05% in seven cases of severe allergic conjunctivitis, found significant reductions in the symptom and sign scores, and a reduction in the demand for corticosteroids, with no side effects observed. (19) In a placebo-controlled, doublemasked study, no significant difference was detected in the symptom, sign and drug scores of the 40 patients with either AKC or VKC after three months of treatment with topical CsA 0.05%; no side effects were reported.…”
Section: A 2bmentioning
confidence: 99%
See 1 more Smart Citation
“…(18) There are several studies about low-dose topical CsA therapy for AKC and VKC. (9,(19)(20)(21) A study by Ozcan et al, which examined the use of topical CsA 0.05% in seven cases of severe allergic conjunctivitis, found significant reductions in the symptom and sign scores, and a reduction in the demand for corticosteroids, with no side effects observed. (19) In a placebo-controlled, doublemasked study, no significant difference was detected in the symptom, sign and drug scores of the 40 patients with either AKC or VKC after three months of treatment with topical CsA 0.05%; no side effects were reported.…”
Section: A 2bmentioning
confidence: 99%
“…(9) Keklikci et al reported reductions in the clinical scores and inflammatory cell counts (using conjunctival impression cytology) of 54 patients after three months of topical CsA 0.05% therapy, with no side effects. (20) A study conducted by Takamura et al, involving 2,597 patients with VKC who were treated with CsA 0.1% for six months, reported decreased clinical scores and the disappearance of steroid demand in one-third of the patients; additionally, 7.4% of them experienced ocular irritation and 1.4% had ocular infections. (21) In the present study, the use of CsA 0.05% resulted in reduced steroid demand, with no serious side effects detected.…”
Section: A 2bmentioning
confidence: 99%
“…Several comparative studies between antiallergy medications and design model studies suggested topical treatment of Olopatadine hydrochloride for use in allergic eye diseases. The effects of Olopatadine in the treatment of allergic conjunctivitis on signs such as itching and redness were shown [14][15][16]. When the antihistaminic medications were compared, it was reported that Olopatadine hydrochloride 0.1% caused less discomfort for patients during the use of the drug [3].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that Cyclosporine A is effective in causing regression of the objective symptoms, particularly the giant papillae on the tarsal conjunctiva due to VKC [26,27]. The inhibitory effect of Cyclosporine A in the development of conjunctival fibrosis is previously known [16]. Cyclosporine A inhibits the development of corneal vascularization [28].…”
Section: Discussionmentioning
confidence: 99%
“…The low dose (cyclosporine A 0.05%) had mixed results in the alleviation of ocular itching and/or other symptoms of chronic AC [Akpek et al 2004;Kosrirukvongs and Luengchaichawange, 2004;Daniell et al 2006;Keklikci et al 2008;Erdinest and Solomon, 2014;Wu et al 2014]. Tacrolimus, with a potency 100-fold that of cyclosporine, blocks cellular steroid receptors, inhibiting mediator release from mast cells and, thereby, suppressing T-cell activation and consequent B-cell proliferation (late-phase allergic responses) [Sawada et al 1987;Erdinest and Solomon, 2014].…”
Section: Immunomodulatorsmentioning
confidence: 99%